2011
DOI: 10.1038/onc.2011.6
|View full text |Cite
|
Sign up to set email alerts
|

E-cadherin inhibits tumor cell growth by suppressing PI3K/Akt signaling via β-catenin-Egr1-mediated PTEN expression

Abstract: E-cadherin is a cell-cell adhesion protein and tumor suppressor that is silenced in many malignancies. E-cadherin is thought to suppress tumor cell growth by antagonizing b-catenin signaling. However, the role of E-cadherin in ovarian cancer progression is still controversial. In this study, we showed that loss of E-cadherin induced ovarian cancer cell growth and constitutive activation of phosphoinositide 3-kinase (PI3K)/Akt signaling by the inhibition of phosphatase and tensin homolog (PTEN) transcription th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
79
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(82 citation statements)
references
References 56 publications
2
79
0
1
Order By: Relevance
“…The present study hypothesized that UHRF1 may inhibit the expression of Rb1 and thereby suppress the expression of E-cadherin. E-cadherin is known to suppress the invasion of cancer cells (25). Therefore, the UHRF1-mediated promotion of invasion may be the result of E-cadherin inhibition.…”
Section: Uhrf1 Suppresses the Expression Of E-cadherin And Promotes Ementioning
confidence: 99%
“…The present study hypothesized that UHRF1 may inhibit the expression of Rb1 and thereby suppress the expression of E-cadherin. E-cadherin is known to suppress the invasion of cancer cells (25). Therefore, the UHRF1-mediated promotion of invasion may be the result of E-cadherin inhibition.…”
Section: Uhrf1 Suppresses the Expression Of E-cadherin And Promotes Ementioning
confidence: 99%
“…The anchorage-independent growth of cancer cells is one of the hallmarks of malignant phenotypes and promoted by loss of E-cadherin (18). Soft agar assays revealed that PLCδ1 reduced the anchorage-independent cell growth of SW620 cells (Fig.…”
Section: Plcδ1 Suppresses Anchorage-independent Cell Growth Andmentioning
confidence: 99%
“…Although research findings have been accumulating to reveal the ubiquitous expression of E-cadherin and its exact role in ovarian cancers, there are still many opposite opinions [20] as well as lots of unsolved questions. For instance, Sawada reported that loss of E-cadherin promotes ovarian cancer cells metastasis via alpha 5-integrin [31] .…”
Section: Wwwchinapharcom Dong Ll Et Almentioning
confidence: 99%
“…However, the mechanism that how E-cadherin plays its role during the development of ovarian cancer still remains unclear. Moreover, contradictory data have suggested that E-cadherin could inhibit tumor cell growth by suppressing phosphatidylinositol 3-kinase (PI3K)/ Akt signaling in ovarian cancer cells [20] . In the present study, to determine the possible functions of E-cadherin in ovarian cancer cells, we knocked down the CDH1 gene expression via RNA interference (RNAi) in the SKOV-3 ovarian cancer cells.…”
Section: Introductionmentioning
confidence: 99%